Peningkatan Pemahaman Nilai Agama Anak Melalui Pembelajaran Berbasis Miniatur Ibadah Pada Anak Usia 4-5 Tahun - Tanti Ratna Ratna Dewi; Rika Partika Sari; Lydia Margaretha (Early Childhood Research and Practice, 2026)
This study was motivated by the low level of understanding regarding religious values ​​among children aged 4–5 years at PAUD Kasih. The children still struggled to recognize items used for worship, imitate simple acts of worship, and recite short prayers. The study aimed to enhance the children's understanding of religious values ​​through instruction utilizing worship miniatures. A Classroom Action Research (CAR) design was employed, conducted over two cycles; each cycle comprised the stages of planning, implementation, observation, and reflection. The research subjects consisted of 12 children aged 4–5 years at PAUD Kasih. Data were collected through observation and documentation and analyzed using both quantitative and qualitative descriptive methods. The results indicate that the use of worship miniatures as a learning medium improved the children's understanding of religious values. In Cycle I, Meeting 1, the achievement rate was 40.10%, falling into the "Beginning to Develop" (MB) category. In Cycle I, Meeting 2, this increased to 53.64%, placing it in the "Developing as Expected" (BSH) category. Subsequently, in Cycle II, Meeting 1, the rate rose to 62.5% (BSH category), and in Cycle II, Meeting 2, it reached 81.25%, falling into the "Developing Very Well" (BSB) category. These results demonstrate that the study's success indicators were achieved. Thus, instruction based on worship miniatures proved effective in enhancing the understanding of religious values ​​among children aged 4–5 years at PAUD Kasih.